Faktorer som påverkar magnesiumabsorptionen i våmmen hos kor - Wallström, Emily (2010)
In metabolism Mg plays an important role because it affects many cellular enzymes in the body. The energy metabolism and protein synthesis are dependent on Mg as an enzyme activator, Mg is also involved in the synthesis of RNA and DNA. Absorption of Mg primarily takes place over the ruminal epithelium in ruminants. The main storage of Mg is in the bones but that can only be reached if the cow is in great need of calcium or phosphorus, it's a hormonal regulated process that induces catabolism of bones. Free and available sources of Mg are found in soft tissues and in the extra cellular fluids that includes cerebrospinal fluids and blood. Free Mg in serum is present in two forms, either bound to protein or free and ionized.